Prediction and analysis of flow behavior during gas kicks considering wellbore–formation coupling and gas solubility - Su, Yu; Ma, Huiyun; Xia, Lianbin; Peng, Chi; Guo, Jianhua; Shen, Xinyu; Fu, Jianhong; Tang, Yijia (Frontiers in Earth Science, 2025)
A gas kick is one of the most dangerous phenomena during petroleum drilling operations, which, if not detected and handled in time, can result in hazardous blowout. To better understand and describe the behavior of gas kicks, this study presents a novel transient flow model by taking wellbore–formation coupling and gas solubility into account during drilling operations. Then, the main flow parameters such as gas void fraction, mixture velocity, and mixture density are analyzed in cases that do or do not consider the coupling effects. Furthermore, the flow behaviors for both oil-based mud (OBM) and water-based mud (WBM) are investigated for comparison. Finally, the reliable indicators of monitoring gas kicks in OBM and WBM drilling are discussed. The results indicate that the gas void fraction increases after an initial decrease with the increased wellbore depth with coupling effects, while it constantly decreases with the increase in the well depth with non-coupling effects. The variation in bottom-hole pressure (BHP) with gas kick time is similar in both cases. Both the mixture velocity and mixture density change more significantly in the middle–lower part of the wellbore compared with non-coupling effects. In particular, the performances of the surface response to a gas kick are quite different compared to the WBM under similar conditions in OBM drilling, and the potentially dangerous gas kick is easily neglected. More importantly, it is confirmed that pit gain is more beneficial for detecting gas kicks compared with the annulus return flow rate (ARFR) for WBM, but neither of these indicators is suitable for gas kick detection in OBM drilling. The results identify pit gain as a reliable indicator for detecting gas kicks in WBM drilling, while real-time bottom-hole pressure (BHP) monitoring is emphasized for OBM drilling under low influx rates.